The Analysis of Questions Item Quality in Mataram University - Memy Wardani Elthia; Bidari Andaru Widhi (ANFA MEDIATAMA, 2023)
This study aimed to determine the difficulty level, distinguishing power, and distractor effectiveness of the Final Examination Questions in Grammer Subjects in the third semester of Mataram University Academic Year 2020/2021.It used descriptive quantitative. The subject of the research is the third semester of the An English Education Department of Mataram University, which are 30 students. The data was collected using the questionnaire method. Then, the data analysis was analyzed by Mrs. Excell.The analysis shows that: Difficulty levels, the number of multiple choice questions classified as easy questions amounted to 1 item, medium category 25 items, and difficult category 24 items. Then, for distinguishing power included of poor categories are 30 items multiple choices questions, the satisfactory categories are 10 items, and the good category is 0, none categories are 4 items, then negative categories are 5 items. While, for the effectiveness of distractors, 120 distractors are accepted or functioning. Then, 32 distractors are revised or not functioning. Therefore, according to the explanation that has been explained, it can be concluded that the Final Examination for the Grammer subject at University of Mataram in the 2020/2021 academic year is including the quality of the unfavorable questions.